Commits

rbeezer committed e9a66c3

Hand-tune text macro replacements

Comments (0)

Files changed (4)

src/section-ILT.xml

 <![CDATA[&\Rightarrow&\lt{S}{\lt{T}{\vect{x}}}&=\lt{S}{\lt{T}{\vect{y}}}]]>
 <![CDATA[&&]]><acroref type="definition" acro="LTC" />\\
 <![CDATA[&\Rightarrow&\lt{T}{\vect{x}}&=\lt{T}{\vect{y}}]]>
-<![CDATA[&&]]><acroref type="definition" acro="ILT" /> for $S$\\
+<![CDATA[&&]]><acroref type="definition" acro="ILT" />\text{ for }S\\
 <![CDATA[&\Rightarrow&\vect{x}&=\vect{y}]]>
-<![CDATA[&&]]><acroref type="definition" acro="ILT" /> for $T$
+<![CDATA[&&]]><acroref type="definition" acro="ILT" />\text{ for }T
 </alignmath>
 </p>
 

src/section-LT.xml

 <alignmath>
 \lt{T}{\zerovector_U}
 <![CDATA[&=\lt{T}{0\zerovector_U}]]>
-<![CDATA[&&]]><acroref type="theorem" acro="ZSSM" /> in $U$\\
+<![CDATA[&&]]><acroref type="theorem" acro="ZSSM" />\text{ in }U\\
 <![CDATA[&=0\lt{T}{\zerovector_U}]]>
 <![CDATA[&&]]><acroref type="definition" acro="LT" />\\
 <![CDATA[&=\zerovector_V]]>
-<![CDATA[&&]]><acroref type="theorem" acro="ZSSM" /> in $V$
+<![CDATA[&&]]><acroref type="theorem" acro="ZSSM" />\text{ in }V
 </alignmath>
 </p>
 
 <![CDATA[\lt{(T+S)}{\vect{x}+\vect{y}}&=]]>
 <![CDATA[\lt{T}{\vect{x}+\vect{y}}+\lt{S}{\vect{x}+\vect{y}}&&]]><acroref type="definition" acro="LTA" />\\
 <![CDATA[&=\lt{T}{\vect{x}}+\lt{T}{\vect{y}}+\lt{S}{\vect{x}}+\lt{S}{\vect{y}}&&]]><acroref type="definition" acro="LT" />\\
-<![CDATA[&=\lt{T}{\vect{x}}+\lt{S}{\vect{x}}+\lt{T}{\vect{y}}+\lt{S}{\vect{y}}&&]]><acroref type="property" acro="C" /> in $V$\\
+<![CDATA[&=\lt{T}{\vect{x}}+\lt{S}{\vect{x}}+\lt{T}{\vect{y}}+\lt{S}{\vect{y}}&&]]><acroref type="property" acro="C" />\text{ in }V\\
 <![CDATA[&=\lt{(T+S)}{\vect{x}}+\lt{(T+S)}{\vect{y}}&&]]><acroref type="definition" acro="LTA" />\\
 <intertext>and</intertext>
 <![CDATA[\lt{(T+S)}{\alpha\vect{x}}&=]]>
 <![CDATA[\lt{T}{\alpha\vect{x}}+\lt{S}{\alpha\vect{x}}&&]]><acroref type="definition" acro="LTA" />\\
 <![CDATA[&=\alpha\lt{T}{\vect{x}}+\alpha\lt{S}{\vect{x}}&&]]><acroref type="definition" acro="LT" />\\
-<![CDATA[&=\alpha\left(\lt{T}{\vect{x}}+\lt{S}{\vect{x}}\right)&&]]><acroref type="property" acro="DVA" /> in $V$\\
+<![CDATA[&=\alpha\left(\lt{T}{\vect{x}}+\lt{S}{\vect{x}}\right)&&]]><acroref type="property" acro="DVA" />\text{ in }V\\
 <![CDATA[&=\alpha\lt{(T+S)}{\vect{x}}&&]]><acroref type="definition" acro="LTA" />\\
 </alignmath>
 </p>
 <![CDATA[\lt{(\alpha T)}{\vect{x}+\vect{y}}&=]]>
 <![CDATA[\alpha\left(\lt{T}{\vect{x}+\vect{y}}\right)&&]]><acroref type="definition" acro="LTSM" />\\
 <![CDATA[&=\alpha\left(\lt{T}{\vect{x}}+\lt{T}{\vect{y}}\right)&&]]><acroref type="definition" acro="LT" />\\
-<![CDATA[&=\alpha\lt{T}{\vect{x}}+\alpha\lt{T}{\vect{y}}&&]]><acroref type="property" acro="DVA" /> in $V$\\
+<![CDATA[&=\alpha\lt{T}{\vect{x}}+\alpha\lt{T}{\vect{y}}&&]]><acroref type="property" acro="DVA" />\text{ in }V\\
 <![CDATA[&=\lt{(\alpha T)}{\vect{x}}+\lt{(\alpha T)}{\vect{y}}&&]]><acroref type="definition" acro="LTSM" />\\
 <intertext>and</intertext>
 <![CDATA[\lt{(\alpha T)}{\beta\vect{x}}&=]]>
 <![CDATA[\alpha\lt{T}{\beta\vect{x}}&&]]><acroref type="definition" acro="LTSM" />\\
 <![CDATA[&=\alpha\left(\beta\lt{T}{\vect{x}}\right)&&]]><acroref type="definition" acro="LT" />\\
-<![CDATA[&=\left(\alpha\beta\right)\lt{T}{\vect{x}}&&]]><acroref type="property" acro="SMA" /> in $V$\\
+<![CDATA[&=\left(\alpha\beta\right)\lt{T}{\vect{x}}&&]]><acroref type="property" acro="SMA" />\text{ in }V\\
 <![CDATA[&=\left(\beta\alpha\right)\lt{T}{\vect{x}}&&\text{Commutativity in $\complex{}$}\\]]>
-<![CDATA[&=\beta\left(\alpha\lt{T}{\vect{x}}\right)&&]]><acroref type="property" acro="SMA" /> in $V$\\
+<![CDATA[&=\beta\left(\alpha\lt{T}{\vect{x}}\right)&&]]><acroref type="property" acro="SMA" />\text{ in }V\\
 <![CDATA[&=\beta\left(\lt{(\alpha T)}{\vect{x}}\right)&&]]><acroref type="definition" acro="LTSM" />\\
 </alignmath>
 </p>
 <alignmath>
 \lt{(\compose{S}{T})}{\vect{x}+\vect{y}}
 <![CDATA[&=\lt{S}{\lt{T}{\vect{x}+\vect{y}}}&&]]><acroref type="definition" acro="LTC" />\\
-<![CDATA[&=\lt{S}{\lt{T}{\vect{x}}+\lt{T}{\vect{y}}}&&]]><acroref type="definition" acro="LT" /> for $T$\\
-<![CDATA[&=\lt{S}{\lt{T}{\vect{x}}}+\lt{S}{\lt{T}{\vect{y}}}&&]]><acroref type="definition" acro="LT" /> for $S$\\
+<![CDATA[&=\lt{S}{\lt{T}{\vect{x}}+\lt{T}{\vect{y}}}&&]]><acroref type="definition" acro="LT" />\text{ for }T\\
+<![CDATA[&=\lt{S}{\lt{T}{\vect{x}}}+\lt{S}{\lt{T}{\vect{y}}}&&]]><acroref type="definition" acro="LT" />\text{ for }S\\
 <![CDATA[&=\lt{(\compose{S}{T})}{\vect{x}}+\lt{(\compose{S}{T})}{\vect{y}}&&]]><acroref type="definition" acro="LTC" />
 <intertext>and</intertext>
 \lt{(\compose{S}{T})}{\alpha\vect{x}}
 <![CDATA[&=\lt{S}{\lt{T}{\alpha\vect{x}}}&&]]><acroref type="definition" acro="LTC" />\\
-<![CDATA[&=\lt{S}{\alpha\lt{T}{\vect{x}}}&&]]><acroref type="definition" acro="LT" /> for $T$\\
-<![CDATA[&=\alpha\lt{S}{\lt{T}{\vect{x}}}&&]]><acroref type="definition" acro="LT" /> for $S$\\
+<![CDATA[&=\lt{S}{\alpha\lt{T}{\vect{x}}}&&]]><acroref type="definition" acro="LT" />\text{ for }T\\
+<![CDATA[&=\alpha\lt{S}{\lt{T}{\vect{x}}}&&]]><acroref type="definition" acro="LT" />\text{ for }S\\
 <![CDATA[&=\alpha\lt{(\compose{S}{T})}{\vect{x}}&&]]><acroref type="definition" acro="LTC" />
 </alignmath>
 </p>

src/section-S.xml

 <p>We will then verify the three conditions of <acroref type="theorem" acro="TSS" />.  First,
 <alignmath>
 \zerovector
-<![CDATA[&=\zerovector+\zerovector+\zerovector+\ldots+\zerovector&&]]><acroref type="property" acro="Z" /> for $V$\\
+<![CDATA[&=\zerovector+\zerovector+\zerovector+\ldots+\zerovector&&]]><acroref type="property" acro="Z" />\\
 <![CDATA[&=0\vect{u}_1+0\vect{u}_2+0\vect{u}_3+\cdots+0\vect{u}_t&&]]><acroref type="theorem" acro="ZSSM" />
 </alignmath>
 </p>

src/section-VS.xml

 <alignmath>
 \zerovector_1
 <![CDATA[&=\zerovector_1+\zerovector_2]]>
-<![CDATA[&&]]><acroref type="property" acro="Z" /> for $\zerovector_2$\\
+<![CDATA[&&]]><acroref type="property" acro="Z" />\text{ for }\zerovector_2\\
 <![CDATA[&=\zerovector_2+\zerovector_1]]>
 <![CDATA[&&]]><acroref type="property" acro="C" />\\
 <![CDATA[&=\zerovector_2]]>
-<![CDATA[&&]]><acroref type="property" acro="Z" /> for $\zerovector_1$
+<![CDATA[&&]]><acroref type="property" acro="Z" />\text{ for }\zerovector_1
 </alignmath>
 </p>